Residue dissipation and dietary risk assessment of fluopyram and its metabolite (M25) in melon. Issue 19 (30th December 2022) - Yizhi, Feng; Aijuan, Zhang; Jinju, Pan; Bojun, Zuo; Lin, Liang
ABSTRACT: The aim of this study was to investigate the dissipation and residues of fluopyram in melon under field conditions and to assess its safe use. A liquid chromatography tandem mass spectrometry (LC-MS/MS) with QuEChERS for analysis of fluopyram and its metabolite M25 was established. Under the experimental condition of adding different levels of analytes (0.02 2 mg kg −1 ), the average residue recovery of fluopyram and M25 in melon was 96% 105% with a relative standard deviation of 2% 8%. The limit of quantitation of fluopyram and M25 in melon was 0.02 mg kg −1 . Field trial results showed that the half-life of fluopyram in melon was 4.5–6.2 days, and the degradation was relatively fast. The residual of M25 in melon was lower than the LOQ. The terminal residues of fluopyram in melon sample were in the range of <0.02 0.095 mg kg −1, which was lower than the maximum residue limit for melon in EU (0.4 mg kg −1 ) and South Korea (0.6 mg kg −1 ). Dietary risk assessment indicated that the long-term intake risk quotient (rqchronic ) and short-term intake risk quotient (rqacute ) of fluopyram in people from different age groups were 0.000079 0.000671 and 0.002978 0.025268, respectively, which were significantly lower than 1. Therefore, the residues of fluopyram in melons would not affect the health of the general population in China.